Assessing organizational framework conditions for the successful, human-centered introduction of AI applications - Andrea Altepost; Farah Elaroussi; Adjan Hansen-Ampah; Markus Harlacher; Wolfgang Merx (Zeitschrift für Arbeitswissenschaft, 2024)
Abstract As part of WIRKsam Competence Center, the authors aim to identify and improve organizational conditions in companies that are conducive to the successful introduction of AI technologies in the workplace. This paper examines various factors that are considered crucial for effective AI integration, including technology acceptance, access to IT infrastructure, workforce structure, organizational culture and participatory practices. Using a~mixed-methods approach, WIRKsam relates the initial organizational conditions to the researchers' assessments and experiences of the first 24~months of the study. The analysis uses both qualitative and quantitative data and provides a~robust framework for identifying the respective organizational prerequisites. It aims to map these factors and provide insights. Our results show the application partners involved in WIRKsam as companies with individual characteristics of technology and AI affinity as well as different organizational cultures. The workforce is predominantly male. Slightly more than half of the employees are 45~years and older. Overall, the research activities in WIRKsam are met with openness to electronic devices and AI. However, the fears of the employees are somewhat underestimated by the researchers. Employees rate their knowledge and experience with regard to AI as low and need support here in order to be able to participate in the participatory design of work systems in a~more informed way. Management support is a~key aspect of technology adoption that employees find important. Their absence is accompanied by worries about the job and lower expectations of positive changes in work, among other things. The knowledge gained will be incorporated into the development of tailor-made action plans to optimize conditions in similar environments. Practical relevance: Using the example of the application companies in WIRKsam Competence Center, the results show that there are very different combinations of framework conditions for the successful introduction of AI into operational practice in companies. Action plans can be derived to individually adapt the integrated approach according to the WIRKsam procedure model. The applied mix of methods allows a~very comprehensive analysis and contributes to the validity of the results. In particular, the survey of researchers contributes to new findings, the importance of which lies on the one hand in complementing the perspective of employees and the company as a~whole, and on the other hand in providing the researchers themselves with a~basis for reflecting on their basic assumptions as an entire research team. @Im Rahmen des Kompetenzzentrums WIRKsam wollen die Autorinnen und Autoren organisatorische Bedingungen in Unternehmen, die für die erfolgreiche Einführung von KI-Technologien am Arbeitsplatz förderlich sind, identifizieren und verbessern. Dieser Beitrag untersucht verschiedene Faktoren, die für eine effektive KI-Integration als entscheidend erachtet werden, darunter Technologieakzeptanz, Zugang zur IT-Infrastruktur, Belegschaftsstruktur, Unternehmenskultur und partizipative Praktiken. Mit einem Mixed-Methods-Ansatz setzt WIRKsam die organisatorischen Ausgangsbedingungen mit den Einschätzungen und Erfahrungen der ersten 24~Monate der Untersuchung aus Sicht der Forschenden in Beziehung. Die Analyse nutzt sowohl qualitative als auch quantitative Daten und bietet einen robusten Rahmen zur Identifizierung der jeweiligen organisationalen Voraussetzungen. Sie zielt darauf ab, diese Faktoren abzubilden und Erkenntnisse zu liefern. Unsere Ergebnisse zeigen die in WIRKsam involvierten Anwendungspartner als Unternehmen mit individuellen Ausprägungen von Technologie- und KI-Affinität sowie unterschiedlichen Organisationskulturen. Die Belegschaften sind überwiegend männlich geprägt. Etwas mehr als die Hälfte der Mitarbeitenden sind 45~Jahre und älter. Insgesamt wird den Forschungsaktivitäten in WIRKsam mit Offenheit für elektronische Geräte sowie KI begegnet. Die Ängste der Mitarbeiter werden von den Forschern jedoch etwas unterschätzt. Mitarbeitende schätzen ihr Wissen und ihre Erfahrung in Bezug auf KI als gering ein und benötigen hier Unterstützung, um sich an der partizipativen Gestaltung von Arbeitssystemen informierter beteiligen zu können. Die Unterstützung durch das Management ist ein zentraler Aspekt der Technologieeinführung, den die Mitarbeiter als wichtig empfinden. Ihre Abwesenheit geht unter anderem mit Sorgen um den Arbeitsplatz und geringeren Erwartungen an positive Veränderungen in der Arbeit einher. Die gewonnenen Erkenntnisse fließen in die Entwicklung passgenauer Maßnahmenpläne zur Optimierung der Bedingungen in ähnlichen Umgebungen ein. Praktische Relevanz: Die Ergebnisse zeigen am Beispiel der Anwendungsunternehmen im Kompetenzzentrum WIRKsam, dass es sehr unterschiedliche Kombinationen von Rahmenbedingungen für eine erfolgreiche Einführung von KI in die betriebliche Praxis in Unternehmen gibt. Anhand dessen können Maßnahmenpläne abgeleitet werden, um die integrierte Vorgehensweise gemäß WIRKsam-Vorgehensmodell individuell zu adaptieren. Der angewandte Methoden-Mix erlaubt eine sehr umfassende Analyse und trägt zur Validität der Ergebnisse bei. Insbesondere die Befragung der Forschenden trägt zu neuen Erkenntnissen bei, deren Bedeutung einerseits darin liegt, die Sichtweise von Mitarbeitenden und Gesamtunternehmen zu ergänzen, andererseits darin, den Forschenden selbst eine Basis zur Reflexion ihrer Grundannahmen als gesamtes Forschungsteam zu bieten.
Keywords: 330; Work design; Artificial intelligence; Organizational framework conditions; Human-centered technology introduction; Arbeitsgestaltung; Künstliche Intelligenz; Organisationale Rahmenbedingungen; Menschzentrierte Technikeinführung